Proceedings of the 1st International Workshop on Pervasive Eye Tracking &Amp; Mobile Eye-Based Interaction 2011
DOI: 10.1145/2029956.2029971
|View full text |Cite
|
Sign up to set email alerts
|

Towards a more effective method for analyzing mobile eye-tracking data

Abstract: In this paper we present the outlines of a new project that aims at developing and implementing effective new methods for analyzing gaze data collected with mobile eyetracking devices. More specifically, we argue for the integration of object recognition algorithms from vision engineering, such as invariant region matching techniques, in gaze analysis software. We present a series of arguments why an object-based approach may provide a significant surplus, in terms of analytical precision, flexibility, additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…However, this approach requires ROI to be defined a priori and any gaze dynamics recorded outside these areas still have to be annotated and processed manually. A potential solution for the processing and analysis of mobile eye-movement data is the use of automatic mapping of the video stream through object recognition algorithms (Brône et al, 2011). Even with these solutions to ROI definition, recording eye movements in a three-dimensional environment also requires accounting for depth, which has not been resolved yet by current mobile eye-tracking systems.…”
Section: Current Challengesmentioning
confidence: 99%
“…However, this approach requires ROI to be defined a priori and any gaze dynamics recorded outside these areas still have to be annotated and processed manually. A potential solution for the processing and analysis of mobile eye-movement data is the use of automatic mapping of the video stream through object recognition algorithms (Brône et al, 2011). Even with these solutions to ROI definition, recording eye movements in a three-dimensional environment also requires accounting for depth, which has not been resolved yet by current mobile eye-tracking systems.…”
Section: Current Challengesmentioning
confidence: 99%
“…For example, Kiefer, Giannopoulos, and Raubal (2014) used mobile eye tracking to analyze pedestrian map usage in an urban context. A number of researchers have also pointed out the potential of integrating location information in the analysis of gaze behavior in real-world environments (Brône, Oben, & Goedemé, 2011;Kiefer et al, 2014;Müller-Feldmeth et al, 2014). More closely related to this article, Ohm, Müller, Ludwig, and Bienk (2014) found that in indoor environments, functional landmarks (i.e., doors and stairs) were more likely to be looked at and named in subsequent route descriptions than, for example, visually obtrusive landmarks (see Viaene et al, 2014, for similar findings).…”
Section: Mobile Eye Tracking In Spatial Cognition Researchmentioning
confidence: 99%
“…Major challenges at the moment are rapid or extreme changes in the lighting conditions, fast movements of the head (and camera), partial occlusions and the speed of the detection algorithms when large sets of common objects are to be identified. Brône, Oben, van Beeck and Goedemé (2011) discussed these main issues and defined the starting-point of their "InSight Out" project, in which they also primarily aim at scientific studies, i.e. offline processing.…”
Section: Gaze Interaction In the Real Worldmentioning
confidence: 99%